2020
DOI: 10.12913/22998624/115513
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Cross-Wedge of a Hollow Rail Axle

Abstract: The article presents an innovative method of manufacturing hollow rail axles using three combined wedge rolls. The proposed solution was evaluated using numerical simulation. Two cases of forming, differing in the wall thickness of the billet, were analysed. The geometry of the formed axles, distributions of the effective strain, temperature and damage function were presented. Moreover, the changes to the forces and torques acting on each roll were presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Numerical simulations were performed using the commercial simulation program Simufact.Forming. This program had been effectively used before for analyzing both cross and skew-rolling processes [11,12,14,[24][25][26]. The numerical results obtained showed a high level of agreement with experimental findings.…”
Section: Materials 2020 13 × For Peer Review 3 Of 21mentioning
confidence: 73%
See 1 more Smart Citation
“…Numerical simulations were performed using the commercial simulation program Simufact.Forming. This program had been effectively used before for analyzing both cross and skew-rolling processes [11,12,14,[24][25][26]. The numerical results obtained showed a high level of agreement with experimental findings.…”
Section: Materials 2020 13 × For Peer Review 3 Of 21mentioning
confidence: 73%
“…This solution allows reducing the diameter of the rolls to 1200 mm, which also causes a significant decrease in torque. For hollow axles, an innovative technique of rolling with three joint rolls was proposed [12], which ensures a rapid removal of cross sectional ovalization. It is also worth noting that in the aforementioned studies, numerical modelling was widely employed or rolling experiments were performed under laboratory conditions (usually, in a scale of 1:5).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of rail axles, however, special joint rolls have to be used, which complicates the forming process. 16) An alternative to the CWR processes may be cross rolling (CR) with three rolls, based on the method of rotary compression of hollow elements [17][18][19] developed and researched in Lublin University of Technology. This process is presented further in this study exemplified by rolling E-and K-class American standard rail axles, shown in Fig.…”
Section: Conception Of a Three Roll Cross Rolling Process Of Hollow Rmentioning
confidence: 99%
“…Problem ten można wyeliminować, korzystając z trzech narzędzi kształtujących (walców). Jednakże -jak wykazano w pracy [7] -ze względu na długość walcowanej osi trzeba wówczas stosować specjalne walce zespolone, co komplikuje przebieg kształtowania.…”
Section: Wprowadzenieunclassified